2017
DOI: 10.11144/javeriana.sc22-2.htcc
|View full text |Cite
|
Sign up to set email alerts
|

High temperature CO2 capture of hydroxyapatite extracted from tilapia scales

Abstract: Hydroxyapatite (HAp) was obtained from tilapia scales by two extraction methods: direct calcination and acid-base treatment. The physicochemical characteristics of the obtained HAps were evaluated by thermogravimetric analysis, X-ray fluorescence, X-ray diffraction, scanning electron microscopy, surface area, infrared spectroscopy, and basicity measurement at 298 K by CO 2 -pulse titration. Furthermore, the CO 2 capture capacity of the solids at high temperature was also determined. Both methods showed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The organic matter which is mainly collagen is present in the centre of the fishbone and in the outer vicinity of the fish scale. The lower crystallinity of the apatite obtained from fish scales by sintering suggests that heat treatment hindered the formation of apatite crystals because of the rapid decomposition of organic matter 39 . Rapid decomposition of the organic matter does not take place in fish bones as the collagen is present in the interior, hence, sintering fish bones result in more crystalline particles than sintering fish scales.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The organic matter which is mainly collagen is present in the centre of the fishbone and in the outer vicinity of the fish scale. The lower crystallinity of the apatite obtained from fish scales by sintering suggests that heat treatment hindered the formation of apatite crystals because of the rapid decomposition of organic matter 39 . Rapid decomposition of the organic matter does not take place in fish bones as the collagen is present in the interior, hence, sintering fish bones result in more crystalline particles than sintering fish scales.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed that acid/base treatment of the fish scales removes the organic matter due to solubilization of proteins and carbohydrates. This resulted in the nucleation and growth of HA during sintering and produced a more crystalline structure than the untreated fish scales 39 . The crystallite size is 13 nm for FS‐0900‐06 and 40 nm for FB‐0900‐06.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst not yet explored in great detail as a potential CO 2 utilisation option, hydroxyapatite has already proven to have application in several fields including aqueous solution remediation, gas detection, agriculture as a fertiliser, ionic conduction and catalysis, [14][15][16][17][18][19][20][21][22] and has been studied as a solid sorbent for carbon capture, with a previous study showing stoichiometric hydroxyapatite can adsorb approximately 0.06-0.07 mmol of CO 2 per gram of material when operating at 650-800 1C. 23,24 Hydroxyapatite, HA, (Ca 10 (PO 4 ) 6 (OH) 2 ) is a widely studied and adaptable calcium phosphate material. Its potential for CO 2 utilisation arises from the fact that the HA crystal structure can accommodate a significant quantity of CO 2 owing to its ability to substitute both hydroxyl (OH À ) and phosphate (PO 4 3À ) groups for carbonate (CO 3 2À ) ions without compromising the crystal structure of the material.…”
Section: Introductionmentioning
confidence: 99%